A precisão possível com GPS L1-C/A em georreferenciamento: o desafio do multicaminho - Palma, Evandro (2005)
Since the creation of the system Navstar/GPS, several sources of observation errors went identified and studied by the scientific community, like as solution of ambiguities, delay ionospheric and non clock synchronous. The problem of the mistake caused by the multipath, however, persists as a challenge, especially for applications that demand larger accuracy and precision. In the case of Brazil, with the promulgation in 2001 of the Law 10267 of the National Cadaster of Rural Properties, this challenge have a specific feature, therefore it influences the applicability of the new cadastral system. The manufacturing companies of GPS receivers has been making great investments in research in that meaning, especially in level of project of receivers. This work analyses the applied technologies in two models of GPS receivers quite a lot used in the State of Rio Grande do Sul, BR, in other words, Ashtech Promark2 and Leica GS20, as well as to analyze the success of those technologies in level of representative field conditions of the reality of geodetic surveys in the State. The results show great potential of use of those receivers to certification works by Instituto Nacional de Colonização e Reforma Agrária (INCRA), as well as they evidences limit situations in that the employment of the same ones is not advised.